Inny jako obcy. Imigranci w polskim dyskursie publicznym i edukacyjnym - Zamojska, Eva (Wydawnictwo Naukowe UAM, 2013)
Taking into account the features of Polish public discourse, dominated by an exclusive perception of what Polish means, one may justifi ably contend that immigrants are the most invisible group of “the others” in Poland, one that is the most excluded from public life. The fi rst part of the article presents the basic theoretical underpinnings of the phenomenon of immigration and ‘being an immigrant’ and attempts to defi ne the uniqueness of this aspect of “otherness”. The second part focuses on a discoursive exclusion of immigrants from public life and the reasons for this exclusion; it moreover proposes possible measures to ameliorate the situation, especially in education.
The Other as a Stranger. Immigrants in Polish Public and Educational Discourse
Keywords: immigrants; politics; discourse; exclusion